Pengaruh Promosi Dan Customer Experience Terhadap Keputusan Pembelian Dengan Rating Sebagai Variabel Intervening: Studi Kasus Pengguna Marketplace Lazada Pada Mahasiswa Manajemen Bp 22 Upi "YPTK" Padang - Puja Permata Widia; Vicky Brama Kumbara; Ai Elis Karlinda (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This research aims to analyze the influence of promotions and customer experience on purchasing decisions with ratings as an intervening variable among Lazada marketplace users among BP 22 UPI "YPTK" Padang management students. The method used is Structural Equation Modeling (SEM) with SmartPLS based on data collected through questionnaires from 100 respondents. The research results show that a). promotion has a positive and significant effect on ratings, b). customer experience has a positive and significant effect on ratings, c). Promotion has a positive and insignificant effect on purchasing decisions. d). customer experience has a positive and significant effect on purchasing decisions, e). ratings have a positive and significant effect on purchasing decisions, f) ratings are able to mediate the relationship between promotions and purchasing decisions. g) ratings are able to mediate the relationship between customer experience and purchasing decisions..